2017
DOI: 10.1299/jtst.2017jtst0004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of film-hole configuration on film-cooling effectiveness of squealer tips

Abstract: Three-dimensional numerical simulations are carried out to investigate the effects of film-hole arrangement and blowing ratio on the squealer tip leakage flow field and tip film-cooling performance. Six film-hole arrangements with 13 holes are designed in the current study for comparison. In type-A and type-B, the film-cooling holes are arranged in a single row, located at the middle camber line or close to the suction-side squealer. The four modified film-hole arrangements are realized by placing two rows of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…For the second type, seven film holes are located in the vicinity of the leading-edge and the remaining six film holes are arranged near the suction-side squealer in the mid-chord region (referred to as LE mode). In previous studies, 20,21) we demonstrated the superiority of the LE mode for improving the film-cooling effect on the squealer tip. In this paper, we continue to explore the effect of trailing-edge cutbacks while considering the relative motion between the blade tip and the casing.…”
Section: Introductionmentioning
confidence: 82%
“…For the second type, seven film holes are located in the vicinity of the leading-edge and the remaining six film holes are arranged near the suction-side squealer in the mid-chord region (referred to as LE mode). In previous studies, 20,21) we demonstrated the superiority of the LE mode for improving the film-cooling effect on the squealer tip. In this paper, we continue to explore the effect of trailing-edge cutbacks while considering the relative motion between the blade tip and the casing.…”
Section: Introductionmentioning
confidence: 82%
“…It is proposed according to pre-simulate of the tip leakage flow field of squealer tip without film-cooling under the condition of stationary casing. And our study (Cheng et al 2017) has described the structural parameter of type-C in detail. Figure 4 presents the definition of the separation line.…”
Section: Calculation Details 21 Computational Modelmentioning
confidence: 99%
“…Table 2 is the summation of the structural parameter of the film-hole arrangements. Cheng, Chang, Jingyang Zhang and Jingzhou Zhang, Journal of Thermal Science and Technology, Vol.12, No.2 (2017) Fig.4 Limiting lines on the squealer tip (Cheng et al, 2017). …”
Section: Calculation Details 21 Computational Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Ameri and Bunker (1999) implemented a computational study to investigate the detailed heat transfer characteristics on the blade tip surfaces for a high-power turbine, and the numerical results were compared with the experimental data of Bunker et al (1999). Cheng et al (2017) studied the effects of film hole location on squealer tip leakage flow, film cooling effectiveness, and surface heat transfer coefficient. The effect of trailing edge cutback on squealer tips was numerically investigated by .…”
Section: Introductionmentioning
confidence: 99%